Analiza shranjevanja toplote v vodonosnikih - možnost uporabe v Sloveniji - Stritih, Uroš (Strojniški vestnik, 2002)
Tendencies towards rational energy use have been appearing for the last decades due to the fact of limited quantities of fossil fuels and increased ecological awareness. Also the rising prices of all fuels should be taken into account. Since energy consumption will increase in the future, the possibility of using renewable energy resources and rational energy use are investigated. The quality of energy exploitation can be increased by storing thermal energy in different types of storage. This is especially important for waste heat from industrial processes, which is usually thrown away. This heat can be efficiently used in low-temperature heating systems. The same holds true for heat from condensing units of air-conditioning systems. ...
Keywords: hranilniki toplote; vodonosniki; prenos toplote; prenos snovi